The Complex Work of Proteases and Secretases in Wallerian Degeneration: Beyond Neuregulin-1 - Pellegatta, Marta; Taveggia, Carla (Frontiers in Cellular Neuroscience, 2019)
After damage, axons in the PNS regenerate and regrow following a process termed Wallerian degeneration, but the regenerative process is often incomplete and usually the system does not reach full recovery. Key steps to the creation of a permissive environment for axonal regrowth are the trans–differentiation of Schwann cells and the remodeling of the extracellular matrix. In this review, we will discuss how proteases and secretases promote effective regeneration and remyelination. We will detail how they control Neuregulin–1 activity at the post–translational level, as the concerted action of alpha, beta and gamma secretases cooperates to balance activating and inhibitory signals necessary for physiological myelination and remyelination. In addition, we will discuss the role of other proteases in nerve repair, among which A Disintegrin And Metalloproteinases and gamma–secretases substrates. Moreover, we will present how Matrix Metalloproteinases and proteases of the blood coagulation cascade participate in forming newly synthetized myelin and in regulating axonal regeneration. Overall, we will highlight how a deeper comprehension of secretases and proteases mechanism of action in Wallerian degeneration might be useful to develop new therapies with the potential of readily and efficiently improve the regenerative process.